Regulated necrosis in COVID-19: A double-edged sword - Sun, Chen; Han, Yunze; Zhang, Ruoyu; Liu, Simon; Wang, Jing; Zhang, Yuqing; Chen, Xuemei; Jiang, Chao; Wang, Junmin; Fan, Xiaochong; Wang, Jian (Frontiers in Immunology, 2022)
COVID-19 caused by SARS-CoV-2 can cause various systemic diseases such as acute pneumonia and cytokine storm. With necroptosis, ferroptosis, and pyroptosis, necrosis constitutes the regulated necrosis patterns under the low apoptosis condition commonly observed in COVID-19. Necrosis is involved in the release of cytokines like TNF-α, IL-1 β, and IL-6 and cell contents such as alarmins, PAMPs, and DAMPs, leading to more severe inflammation. Uncontrolled necrosis may explain the poor prognosis and cytokine storm observed in COVID-19. In this review, the pathophysiology and mechanism of necrosis with the double-edged sword effect in COVID-19 are thoroughly discussed in detail. Furthermore, this review also focuses on the biomarkers and potential therapeutic targets of the necrosis pathway in COVID-19, providing practical guidance to judge the severity of COVID-19, prognosis, and clinical treatment, as well as guiding the development of clinical anti-SARS-CoV-2 drugs.